The Application of Sustainable Development Concept for Tourism Development in Indonesia - Risfandini, Andini; Sunardi, Sunardi (International Conferences SDGs 2030 Challenges and Solutions, 2030)
Tourism is a leading economic sector that generates the growth of world economy. Accelerating tourism development is one of the main priority of the government of Indonesia because tourism is expected to be one of the main sector to increase the GDP of Indonesia by generating jobs for millions of people that still live below the poverty line. The purpose of this article is to determine on how to implement the concept of sustainable development for tourism development in Indonesia effectively. Butler (1999) mentioned that to ensure the implementation of sustainable development in tourism, the concept must be accepted by all the stakeholders (Butler, 1999). How can the stakeholders accept the concept if they do not even understand the meaning of sustainable development in tourism? Before commencing the tourism development in an area, the concept of sustainable development in tourism must be introduced to all stakeholders. The next thing that has to be done by the government is to plan on how to socialize the concept of sustainable tourism development through education, campaign, and seminar. Further research needs to be conducted to identify how to introduce sustainable development concept in tourism through education in Indonesia.